Formation mechanism of A-site complex perovskite (Ba, Sr)TiO3 microplatelets. Issue 2 (1st February 2019) - Wei, Dandan; Li, Wenxuan
Abstract: A-site complex perovskite (Ba, Sr)TiO3 microplatelets with high aspect ratio were synthesized successfully by molten salt synthesis (MSS) and topochemical microcrystal conversion(TMC) technique. In the process of synthesis, Bi4 Ti3 O12 (BiT) platelets firstly prepared by MSS method were used as precursor and powdered SrCO3 -BaCO3 mixture were employed as reactants in NaCl flux at 1000 °C. The effects of BiT-to-SrCO3 -to-BaCO3 molar ratios on phase and microstructure of the resultant products were investigated. The synthetic (Ba0.5 Sr0.5 )TiO3 platelets would be effective templates for producing highly textured ceramics using the templated grain growth(TGG) method.